1986
DOI: 10.1128/aem.51.1.95-100.1986
|View full text |Cite
|
Sign up to set email alerts
|

Energetics of Leucyl-Leucine Hydrolysis in Streptococcus cremoris Wg 2

Abstract: The hydrolysis of the dipeptide leucyl-leucine by whole cells of Streptococcus cremoris Wg2 was dependent on the presence of the energy source lactose. Incubation of cells with uncouplers or ATPase inhibitors prevented the increase of peptidase activity upon the addition of lactose. Incubation with the ionophore nigericin resulted in decreased peptide hydrolysis activity, while incubation with valinomycin led to increased hydrolysis activity. In the presence of nigericin the ApH component of the proton motive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1987
1987
2004
2004

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…A dipeptidase from L. Iactis subsp. cremoris Wg2, which only hydrolyzed dipeptides, has already been purified by van Boven et al (28,31). A peptidase that was able to hydrolyze the synthetic substrate leucyl-p-nitroanilide was also reported for this strain.…”
Section: Discussionmentioning
confidence: 83%
“…A dipeptidase from L. Iactis subsp. cremoris Wg2, which only hydrolyzed dipeptides, has already been purified by van Boven et al (28,31). A peptidase that was able to hydrolyze the synthetic substrate leucyl-p-nitroanilide was also reported for this strain.…”
Section: Discussionmentioning
confidence: 83%
“…3). At a lower external pH, the ApH is larger (30) and the rate of leucyl-['4C]leucine uptake in cells of S. cremoris E8 is higher.…”
Section: Resultsmentioning
confidence: 94%
“…Energy requirement of peptide uptake. In a previous study (30), it was shown that the 'rate of hydrolysis of leucylleucine by S. cremoris depends on the presence of an energy source. This was confirmed by determining the uptake of leucyl-["'C]leucine by S. cremoris E8 in the prese'nce and absence of an energy source (Fig.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Distinct systems exist for amino acid, di-and oligopeptide transport in lactic streptococci [55,82,83; see review 53]. A recent study [84] involving S. cremoris Wg2 confirmed the energy-dependent utilization of dipeptides [83] and showed that the hydrolysis of leucyl-leucine was dependent on a pH gradient across the cell membrane. The rate of hydrolysis was apparently limited by the activity of the uptake system since hydrolysis was markedly accelerated on disruption of the permeability barrier but the results leave open the question as to whether the transport and hydrolysis steps are quite independent or are coupled via a membrane-bound dipeptidase system.…”
Section: Some Growth Of Starter Bacteria In Milk Can Occur Without Prmentioning
confidence: 99%